What Patients, Families, Health Professionals and Hospital Volunteers Told Us about Advance Directives - Carmen WH Chan; Martin MH Wong; Kai Chow Choi; Helen YL Chan; Amy YM Chow; Raymond SK Lo; Michael MK Sham (Elsevier, 2019)
Objective: An advance directive (AD) is a document that allows mentally competent individuals to make healthcare decisions about their condition that they might no longer be able to make in the future. This study aimed to explore the perceptions of AD decision-making of various stakeholders in the Chinese palliative care setting. Methods: Patients with life-limiting diseases, family members, health professionals, and hospital volunteers were recruited in the palliative care unit of two hospitals in Hong Kong by purposive sampling on age and sex. Qualitative semi-structured individual interviews were conducted. Results: A total of 96 participants, including 24 participants from each group, completed the study. Most participants were willing to discuss AD but had not heard about it before the interview. Patients regarded the decisions made in the AD as a way to reduce their future sufferings, while they also considered the welfare of their family. Family members were concerned about the psychological burden when discussing about the AD. Health professionals emphasized the logistic and process of the AD. Hospital volunteers pointed out the impact of Chinese culture on AD acceptance and the lack of AD promotion in the community. Conclusions: The findings of the study indicated the need for more promotion of AD in the society. It is important to consider the opinion of a patient's family during AD discussions in a Chinese culture. Health professionals may need to identify the best timing for the discussion of AD with patients and their families.